2012
DOI: 10.1088/1367-2630/14/3/035015
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic dipole configurations in honeycomb lattices: order and disorder

Abstract: Dipolar spin ice has attracted much attention because of its intriguing ground state ordering and elementary excitation properties. We present experimental realizations of magnetic dipolar spin ice on periodic lattices with honeycomb symmetry. We have analyzed in particular the evolution and distribution of excitations with magnetic charges ±3 per vertex as a function of magnetic field and the distance b between the dipoles ranging from b = 0.4 to 1.7 µm. In all the dipole patterns investigated, we observe a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…4). This is in accordance with the conclusion of Schumann et al [37]: the statistics is independent of the vacancies' concentration. The increase of c ( ) 4 η ± suggests that defective nodes and nodes next to the defects do not longer obey the ice rule; consequently, transitions between close energy levels appear.…”
Section: Randomly Distributed Vacanciessupporting
confidence: 93%
See 1 more Smart Citation
“…4). This is in accordance with the conclusion of Schumann et al [37]: the statistics is independent of the vacancies' concentration. The increase of c ( ) 4 η ± suggests that defective nodes and nodes next to the defects do not longer obey the ice rule; consequently, transitions between close energy levels appear.…”
Section: Randomly Distributed Vacanciessupporting
confidence: 93%
“…There, the hysteresis reveals the importance of disorder. Schumann et al [37] studied defects in kagome spin ice and conclude that patterns with some local defects are still representative of the statistics of more perfect patterns. For square-lattice spin ice Budrikis et al [38] concluded that the strength of disorder is more important than its origin: small perturbations do not vary the essential properties of the system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, artificial spin ice systems were proposed to be constructed as arrays of optical traps [267,268]. A large number of experiments and theories since 2006 have considered artificial spin ice systems, including planes of ferromagnetic islands with square, honeycomb and Kagome lattices [269,270,271,272,273,274,275,276,277,278,279,280,281,282,283,284,285,286,287,288,289,290,291,292,293,294,295]. In particular, it has been shown using magneto-optical Kerr effect that disorder in the roughness (in shape) of magnetic islands plays essential role in the collective behavior of artificial spin ices [296,297].…”
Section: Artificial Spin Icementioning
confidence: 99%
“…During magnetization reversal, their frequency has a peak at the coercivity, independent of the boundary condition. Overall, their frequency is much less (10-20%) when compared with patterns of similar island separation but larger dimension of the dipoles (60-80%) [10,11]. There is, however, a difference with respect to the formation of Dirac strings when crossing the coercive field: many more strings emanate from the border to the interior of the pattern when the hexagons are open at the border than when they are closed.…”
Section: Discussionmentioning
confidence: 98%
“…When crossing the coercive field point, we observe rather different configurations, depending on whether the pattern is terminated with open or closed hexagons. In figure 3, we show MFM maps of both patterns in the [11] orientation taken on the ascending branch crossing the coercivity at an external field of 500 Oe. In patterns with closed hexagons at the edges, only a few dipole strings become visible; one of them is marked by white lines in figure 3a.…”
Section: (A) Field Dependencementioning
confidence: 99%